‘High politics’ and its intellectual contexts - Middleton, A (Wiley, 2021)
Recent interest in the historiography of ‘high politics’ has centred mainly on historians writing in the 1960s and 1970s, above all Maurice Cowling. Less attention has been paid to the modified agendas pursued by the next generation of scholars. This essay explores some pioneering attempts to make sense of the structural relationships between 19th-century British ‘high politics’ and its ‘intellectual’ contexts, focusing on a cluster of seminal 1980s studies by the historians Michael Bentley, Richard Brent, Boyd Hilton, and Jonathan Parry. Together, these works demanded a fundamental rethinking of how Victorian politics operated.